2021
DOI: 10.1177/02654075211054781
|View full text |Cite
|
Sign up to set email alerts
|

Dialing up desire and dampening disinterest: regulating sexual desire in the bedroom and sexual and relationship well-being

Abstract: Romantic partners often regulate their emotions and affection to achieve certain goals, but research has yet to explore how partners regulate their expression of sexual desire during sex and its implications for couples’ well-being. In two multi-part dyadic diary studies of primarily mixed-gender couples in longer-term relationships residing in North America, we examined three questions. First, is amplifying desire and suppressing disinterest during sex associated with both partners’ daily sexual and relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In couples coping with female sexual interest/arousal disorder, when one member of the couple endorsed greater use of reappraisal (i.e., cognitively reframing an emotionally charged situation) to regulate negative emotions about their sexual relationship, their partner reported lower conflict within the relationship (Dubé et al, 2019). In two nonclinical samples of couples, upregulating the expression of sexual desire in the absence of genuine feelings of sexual desire was linked to both partners’ lower sexual satisfaction (Horne et al, 2022). This same study found that people reported higher relationship satisfaction when, during sex, their partner managed feeling low sexual desire by actively concealing their disinterest in sex.…”
Section: Emotion Regulation and Sexual Well-beingmentioning
confidence: 99%
“…In couples coping with female sexual interest/arousal disorder, when one member of the couple endorsed greater use of reappraisal (i.e., cognitively reframing an emotionally charged situation) to regulate negative emotions about their sexual relationship, their partner reported lower conflict within the relationship (Dubé et al, 2019). In two nonclinical samples of couples, upregulating the expression of sexual desire in the absence of genuine feelings of sexual desire was linked to both partners’ lower sexual satisfaction (Horne et al, 2022). This same study found that people reported higher relationship satisfaction when, during sex, their partner managed feeling low sexual desire by actively concealing their disinterest in sex.…”
Section: Emotion Regulation and Sexual Well-beingmentioning
confidence: 99%